Improving the applicability and transparency of land use change modelling: The iCLUE model. (October 2018) - Verweij, P.; Cormont, A.; Kok, K.; van Eupen, M.; Janssen, S.; te Roller, J.; de Winter, W.; Pérez-Soba, M.; Staritsky, I.G.
Abstract: Human use of land increasingly alters the structure and the functioning of the environment. To ex-ante understand and anticipate these changes there is an increased need for readily available and operational land use change models. One of these models is CLUE, which has been used in many studies all over the world. These studies brought forward operational hurdles, that hamper model application. The overall objective of this paper is to present a new version of the CLUE model, iCLUE, that helps to overcome these hurdles. We describe the technical redevelopment, conceptual innovations, several applications and success factors and critical reflections. iCLUE minimizes manual error-prone actions, enhances ease-of-use, speeds up the operational modelling process and provides data visualisations to empower users to analyse and interpret results. Highlights: iCLUE is a new member of the commonly used CLUE land use change model family. Ease of use and model transparency enhance learning opportunities. Inclusion in a modelling framework enables scenario analysis and impact assessment. The software architecture creates opportunity for model enhancements.